High Coping Self-Efficacy Associated With Lower Sweat Inflammatory Cytokines in Adults: A Pilot Study. Issue 1 (January 2020) - Hladek, Melissa; Gill, Jessica; Lai, Chen; Lorig, Kate; Szanton, Sarah
Introduction/Background: Chronic diseases, like diabetes and heart disease, are considered inflammatory conditions with elevated levels of the proinflammatory cytokines interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) and the anti-inflammatory cytokine interleukin-10 (IL-10). Disease progression is not consistent from person to person. Psychosocial factors are hypothesized to play a modifying role. Self-efficacy, the confidence in one's ability to perform well in a specific life domain or at a specific task, is associated with better health outcomes. Coping self-efficacy is confidence in one's ability to handle life's problems through emotional regulation, problem-solving, and social support. Little is known about associations between coping self-efficacy and inflammation. Aim: The purpose of this pilot study was to examine associations between coping self-efficacy and IL-6, IL-10, and TNF-α levels. Method: This was a cross-sectional study conducted over two visits. Sociodemographic variables, chronic disease count, body mass index (BMI), and coping self-efficacy were collected. Inflammatory markers were collected via sweat using the sweat patch, a noninvasive collection device. Results: Higher TNF-α and IL-10 levels were significantly associated with low coping self-efficacy (β = −.03, p = .028; β = −.017, p = .007, respectively) after adjustment for age, sex, race, BMI, and chronic disease count. IL-6 trended toward significance after adjustment as well (β = −.22, p = .054). Conclusions: This pilot study showed that high coping self-efficacy was associated with lower IL-6, IL-10, and TNF-α levels, indicating a potential buffering effect of high coping self-efficacy. Further longitudinal research with larger sample sizes is needed.